Stategies for trade liberalization in the Americas - Chichilnisky, Graciela (UN ECLAC SantiagoCL, 1992)
Reviews the existing economics of trading blocks and presents a new conceptual approach to the economics of preferential trade. Looks at NAFTA, an American free trade zone and global free trade.